Derzhavin's dramaturgy as an artistic system - A.I. Razzhivin (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper considers the drama works created by G.R. Derzhavin, the greatest poet of the turn of the 18th – 19th centuries, in the last decade of his life, during the crisis of Russian drama. The relevance of the research is determined by the growing interest of contemporary literary criticism in the boundary and transitional phenomena in the history of Russian culture, in particular, during the period of Russian pre-Romanticism, and in the dramaturgy of this period as a more static and conservative kind of literature. The research has been performed with the aim of revealing the aesthetics and poetics of the drama in the post-classical period based on G.R. Derzhavin's plays and theoretical works. The evolution of the late G.R. Derzhavin's creative method seems equally important. The typological and comparative historical methods of research have made it possible to distinguish the thematic blocks of G.R. Derzhavin's dramatic works, genre peculiarity (lyrical and philosophical tragedies, theatrical performances with music, operas, play pieces, and other genre formations) and the playwright's original creative manner. The problematic, genre, and textual analyses have allowed arguing about G.R. Derzhavin's artistic dramatic system that includes the synthesis of arts, genre syncretism, elements of dissimilar styles, as well as moral and philosophical ideals, such as virtue, innocence, truth, love, and justice. The identified historical, literary (Russian and foreign), folklore, mythological plot sources are the important obtained results. The latter are the basis for operas, which are thematically associated with the history of G.R. Derzhavin's homeland (Kazan and Volga Bulgaria). The obtained results allow drawing the conclusion that G.R. Derzhavin's plays manifest the intensive pioneering work and reveal the spirit of polemics in relation to his contemporaries and predecessors. Therefore, G.R. Derzhavin's dramaturgy is a no less vivid and large-scale part of his literary heritage, evidencing the evolution of his creative method from classicism to pre-Romanticism.